Resonant Oscillations of Josephson Current in Nb‐Bi2Te2.3Se0.7‐Nb Junctions. Issue 3 (28th January 2022) - Stolyarov, Vasily S.; Roditchev, Dimitri; Gurtovoi, Vladimir L.; Kozlov, Sergey N.; Yakovlev, Dmitriy S.; Skryabina, Olga V.; Vinokur, Valerii M.; Golubov, Alexander A.
Abstract: Josephson proximity junctions and devices employing topological insulators are promising candidates for realizing topological superconductivity and topologically protected quantum circuits. Here, the new type of oscillations of the critical Josephson current in the ballistic Nb‐Bi2 Te2.3 Se0.7 ‐Nb junctions subject to the magnetic fields is reported. The oscillations appear below ≈400 mK and have a very unusual sharp‐peaked shape. Their ultra‐short period ≈1 Oe, by orders of magnitude shorter than the expected periodicity due to fluxoid quantization in the device, corresponds to the extremely low energy scale ≈1 μ eV. It is established that the observed effect is due to the resonant transmission of Andreev quasiparticles via the peculiar energy levels forming near the S‐TI interfaces. Abstract : Unexpectedly fine (≈1 Oe) resonant oscillations of the critical Josephson current in the magnetic field are observed in ballistic Nb‐Bi2 Te2.3 Se0.7 ‐Nb proximity junctions at temperatures below 500 mK. The peaked maxima of oscillations are attributed to the resonant transmission of quasiparticles through low‐lying Andreev bound states forming at the superconductor‐topological insulator interfaces owing to the p ‐wave component of the induced superconducting order.